The Effect of Risk Profile in Pandemi Outbreak to Banking Financial Performance Case Study in Indonesia - abdullah, Fajar (Journal Of Middle East and Islamic Studies, 2023)
The risk profile that occurred within the scope of banking during the Covid 19 pandemic which was quantitatively reflected in the microeconomic ratios of the BOPO, NPF/NPL, FDR/LDR ratios, and macroeconomics in this case, inflation and the USD exchange rate, were the main factors in the decline in the soundness level bank which is reflected in the value of the bank's financial performance ratio, namely Return on Assets due to. The objects in this study are the general Islamic and conventional banking industry, with data observations including BOPO, NPF/NPL, FDR/LDR, inflation, and the USD exchange rate. By comparing the effect between variables before and during the Covid 19 pandemic.The results of this study prove that the risk profile factors expressed by BOPO, FDR/LDR, and inflation are significant and tend to increase their influence during the Covid 19 pandemic.